Contacts with health services for COVID-19-related reasons during the first wave of the pandemic in Portugal: a longitudinal study - Henrique Barros; Raquel Duarte; Raquel Lucas; Teresa Leão; Sílvia Fraga; Milton Severo; Elisabete Ramos; Susana Silva; Ana Isabel Ribeiro; Nuno Lunet; Joana Araújo; Paula Meireles; et al. (BMJ Public Health, 2024)
Introduction Access to COVID-19-related care during the pandemic deserve attention and study to inform future strategies to deal with similar health emergencies in the future. We aimed to describe access to care for COVID-19-related reasons during the first 9 weeks of the pandemic in Portugal, to quantify the frequency of remote and in-person contacts with healthcare for COVID-19-related reasons and to assess the association between individual and context characteristics and contacts with health services.Methods We conducted an internet-based open cohort study with a non-probabilistic sample of 12 006 persons aged 16 years or more. One questionnaire was sent daily from 23 March 2020 for 9 weeks.Results General practitioners (GPs) were the main points of contact of patients with health services for COVID-19-related reasons. In our population, the main drivers found for any difference in the probability of contact with health services for COVID-19-related reasons were perceived high-risk contacts, followed by the existence of COVID-19 main symptoms. There were 17% more (0.17, 95% CI 0.15 to 0.18) contacts with health services among participants who reported personal contact with a confirmed case, 7% more (0.07, 95%CI 0.06 to 0.07) contacts if the contact had been with a suspected case and 6% more (0.06, 95%CI 0.05 to 0.07) contacts among participants who reported COVID-19 main symptoms in the previous 24 hours. Sociodemographic and household factors were not associated with major differences in healthcare contacts. The probability of contact with any health service for COVID-19-related reasons was highest at the beginning of the pandemic.Conclusion Most contacts with health services for COVID-19-related reasons during the first wave of the pandemic were with GPs, highlighting the role of first-contact care with these clinicians in Portuguese Primary Care, particularly in the context of the COVID-19 pandemic. Sociodemographic and household factors were not associated with major risk differences, suggesting that universal coverage and equity worked in our study sample at this pandemic stage.